PENGARUH MEDIA SHORTIR SHAPES TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 4-5 TAHUN DI TK SEKAR INSANI - Ekayati, Ifa Aristia Sandra; Pertiwi, Novia Ayu Sekar; sumadi (GCEJ (Golden Childhood Education Journal), 2024)
A study based on common problems in early childhood education. The purpose of this study was to clarify the cognitive development of children, their ability to use media shorting shapes and the gradual effect of media shorting shapes on their cognitive development in Sekar Insani Kindergarten in 2022/2023. That is. This type of research is experimental research with a quantitative approach. The results showed that the media shorting shapes had an effect on the cognitive abilities of children in Sekar Insani Kindergarten. These data are the results of learning in the experimental class, and the results of children's language development are obtained with the average score of children on the pretest 1.83 and the average score of children on the posttest 3.3 With a maximum score of 4 and a minimum score of 1 after the test, children's language development in the experimental class was superior to the control class. The cognitive development of the control class children obtained an average pretest score of 1.25 and an average posttest score of 2.25, with a maximum score of 4 and a minimum score of 1. These data are also from hypothesis testing. The test score is 2.56 > 2.021 with a significant number = 0.05. Therefore, the hypothesis Ho is rejected and Ha is accepted. Therefore, it can be said that media shortening shapes greatly affect the cognitive development of children in Sekar Insani Kindergarten